Susanna Moodie : Letters of a Lifetime. - Moodie, Susanna (University of Toronto Press, 1993)
First published in 1985, this volume of letters follows Susanna Moodie from her Suffolk girlhood and her experience as an aspiring young writer in London, through her emigration to Upper Canada and five decades of Canadian life.